Investigation of the Impact of Generator Tripping on Transient Stability in a Two-Generator Power System - Muhira Dzar Faraby; Sofyan Sofyan; Muh. Asri Fajri; Fathir Ramadhan; Muhammad Syahrir; Muh. Hafizh Zuhri; Sry Winarni (Journal FORTEI-JEERI, 2025)
Transient stability is a crucial aspect of power systems that determines the system’s ability to maintain synchronization after experiencing a sudden major disturbance. This study analyzes the response of the IEEE 30-Bus system to the scenario of tripping one of the two generators at the 1st second, simulated using the Electrical Transient Analyzer Program (ETAP 21). The system was modeled with two generators, where Generator 1 acts as the swing generator and Generator 2 as the voltage control generator, supported by 21 loads and two motors controlled by PWM and VFD. The case study focused on the disconnection of Generator 1, with system frequency response observed from the 1st to the 30th second. Results showed that system frequency dropped from 50 Hz to 49.4 Hz, then increased and stabilized at 49.7 Hz (99.4% of the initial condition) due to the inertia and governor action of the remaining generator. These findings highlight the importance of software-based transient studies in understanding the dynamic characteristics of power systems and in designing effective mitigation strategies